The body as theology in pastoral psychology - Gibson, Terrill L. (Journal of religion and health, 1981)
The physical body is explored as a metaphor of transformation and healing in pastoral psychotherapy. Three sections of the paper outline 1) the perception of the body as a point of critical clinical intervention, 2) the understanding of body as a living image of soul, and 3) the body as corporal participant in the mystical Body of Christ. Primary concern focuses on correcting possible misperceptions (among both secular and pastoral "bodyists") of bodily dysfunction as retribution for sinful existence rather than, more biblically, as signaling an opportunity for the inrushing of healing, divine grace. A brief clinical example highlights some possible theoretical and methodological consequences of this clinical world view.